MENANTI KINERJA KEPALA MADRASAH SEBAGAI HASIL PELATIHAN PARTISIPATIF - Yudha Andana Prawira (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2021)
This research is based on the need to improve the proficiency and performance of the Madrasah Principles. The participants of the main Madrasah training already have their respective competencies. A strategy for adult education is therefore needed to promote higher competence. One form of training is known as participatory training. The data obtained were then analyzed using a quantitative approach so that some results could be reported, the results of the training which, in addition to the competence of the head of the madrasah, also included a tendency towards positive results as a result of the participatory training found other things that could improve the performance of this madrasah school principal influenced by work experience and educational background factors. Other results suggest that the proficiency of madrasah school principals who are in the moderate madrasa class category may be different from the proficiency and performance of madrasah principals who are in the high madrasa category due to their different educational backgrounds -Class lie, exceeds. These are the results of this analysis as an application of the participatory training model in the training of Madrasah school leaders.Keywords: Madrasah Principles, competency; participative trainingAbstrak Penelitian ini didasari atas perlunya peningkatan kompetensi dan kinerja kepala madrash. Peserta pelatihan kepala madrasah telah memiliki kompetensi masing-masing, karena itu, untuk mendorong kompetensi yang lebih tinggi dibutuhkan strategi pelatihan orang dewasa. Salah satu bentuk pelatihannya dikenal dengan sebutan pelatihan partisipatif. Data yang didapatkan selanjutnya dianalisis dengan pendekatan kuantitatif, maka dapat dikemukakan beberapa hasil, temuan hasil pelatihan yang antara lain bahwa selain kompetensi kepala madrasah yang menunjukkan kecenderungan hasil positif sebagai akibat pelatihan partisipaitf, juga ditemukan beberapa hal lain yang bisa meningkatkan kinerja kepala madrasah ini yang dipengaruhi oleh faktor pengalaman kerja dan latar belakang pendidikan. Temuan lainnya menunjukkan bahwa bisa terjadi kompetensi kepala madrasah yang berada pada kategori madrasah sedang melebihi kompetensi dan kinerja daripada kepala madrasah yang berada pada kategori madrasah tinggi yang disebabkan berbeda latar belakang pendidikan. Demikian temuan dan hasil analisis ini, sebagai dampak dari sebuah aplikasi atas model pelatihan partisipatif dalam pelatihan kepala madrasah pelatihan. Kata Kunci: kepala madrasah; kompeten; pelatihan partisipatif